2022
DOI: 10.1007/s40831-022-00612-x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal De-coating Pre-treatment for Loose or Compacted Aluminum Scrap and Consequences for Salt-Flux Recycling

Abstract: In aluminum recycling, thermal de-coating pre-treatments remove moisture and organic contamination before re-melting. If the scrap is compacted into bales or briquettes before the thermal treatment and re-melting processes, less surface area is exposed to oxidation in contact with air. However, compaction may also limit the efficiency of the de-coating process. In this study, coated sheets of aluminum were thermally de-coated at varied temperatures and durations. Observations of changes in coating thickness, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…The aluminum pieces are then recovered from the crucible by leaching the salt in water and sieving. The coalesced pieces are then observed to assess the extent of coalescence, usually according to [62] Coalescence (%) = Mass of Coalesced Pieces Mass of Scrap Input (4)…”
Section: Assessment Of the Efficiency Of Salt Fluxesmentioning
confidence: 99%
See 1 more Smart Citation
“…The aluminum pieces are then recovered from the crucible by leaching the salt in water and sieving. The coalesced pieces are then observed to assess the extent of coalescence, usually according to [62] Coalescence (%) = Mass of Coalesced Pieces Mass of Scrap Input (4)…”
Section: Assessment Of the Efficiency Of Salt Fluxesmentioning
confidence: 99%
“…The evaluation of the mass of coalesced pieces varies to a great extent in the literature. For example, Vallejo-Olivares et al [62] used the mass of the largest piece recovered, while Capuzzi et al [63] considered the fraction of the coalesced droplets and their average diameters to account for their roundness. Besson et al [18] considered the size of a single molten aluminum chip and chose coalesced pieces that were larger than a certain size limit.…”
Section: Assessment Of the Efficiency Of Salt Fluxesmentioning
confidence: 99%
“…In this treatment, the scrap is heated up to temperatures that allow thermal and chemical decompositions of the coating substrates, through which organic compounds that composed the outermost layer could be removed from the scrap surface through volatilization [9]. The earlier works [10][11][12][13], for instance, showed the importance of thermal de-coating as a pre-treatment during the recycling of Mg-and Al-based materials. Despite simple, this thermalbased treatment could not eliminate inorganic compounds [12].…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 99%
“…The thermal treatment also reduces the risks of health and safety hazards during re-melting, such as the generation of toxic, poisonous, or combustible gases (H 2 S, PH 3 , H 2 and CH 4 ) [9,18]. Moreover, in salt-recycling processes, de-coating promotes the coalescence of the metal droplets, potentially reducing the amount of metal entrapped in the salt slag residue [19][20][21]. However, the volatile organic compounds (VOC's) and other gases generated during the thermal de-coating pre-treatments can also pose health, safety and environmental risks and must be handled adequately, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that pressing coated aluminium chips into briquettes of low densities did not affect its recycling in salts. However, compacting to higher densities by the moderate-pressure torsion (MPT) method limited the de-coating efficiency and metal coalescence [21]. Steglich [25] re-melted used beverage cans (UBCs) without salt-flux and concluded that a thermal de-coating would reduce dross if conditions for stoichiometric thermolysis were applied for at least 30 min at 550-570 °C.…”
Section: Introductionmentioning
confidence: 99%